Multi-Drug-Resistant Gram-Negative Microorganisms: Epidemiology, Treatment and Alternative Approach - Maria Teresa Mascellino (MDPI AG, 2022)
The presence of enzymes such as Extended-Spectrum β-lactamase (ESBL) and carbapenemases (KPCs, Metallo β-lactamases and OXA) constitutes the principal resistance mechanism to antibiotics [...]